Modified Turbo and SDROM Method for Speech Processing for Cochlear Implants - S.Hallikar, Rohini; Uttarakumari, M; K, Padmaraju; D, Yashas (International Journal of Engineering and Technology, 2018)
A performance comparison of Signal Dependent Rank Order Mean (SDROM) method of speech signal enhancement with a speech enhancement method which makes use of a Turbo combination and SDROM filter referred to as modified Turbo and SDROM technique is made in this paper. Normally, speech signals are used as inputs to a cochlear implant signal processing unit.Sounds are corrupted by different noises such as AWGN, Impulsive noise and babble. The results are evaluated in terms of enhancements evaluations done by basically three parameters namely correlation coefficient, log spectral distortion (LSD) and segmental signal to noise ratio(SSNR). These parameters are calculated between the processed and the clean signals.. Results prove the superior performance of the new method especially for AWGN corrupted speech.Â Â Â